Population Genomic Analysis Reveals a Highly Conserved Mitochondrial Genome in Fusarium asiaticum - Yang, Meixin; Zhang, Hao; van der Lee, Theo A. J.; Waalwijk, Cees; van Diepeningen, Anne D.; Feng, Jie; Brankovics, Balázs; Chen, Wanquan (Frontiers in Microbiology, 2020)
Fusarium asiaticum is one of the pivotal members of the Fusarium graminearum species complex (FGSC) causing Fusarium head blight (FHB) on wheat, barley and rice in large parts of Asia. Besides resulting in yield losses, FHB also causes the accumulation of mycotoxins such as nivalenol (NIV) and deoxynivalenol (DON). The aim of this study was to conduct population studies on F. asiaticum from Southern China through mitochondrial genome analyses. All strains were isolated from wheat or rice from several geographic areas in seven provinces in Southern China. Based on geographic location and host, 210 isolates were selected for next generation sequencing, and their mitogenomes were assembled by GRAbB and annotated to explore the mitochondrial genome variability of F. asiaticum. The F. asiaticum mitogenome proves extremely conserved and variation is mainly caused by absence/presence of introns harboring homing endonuclease genes. These variations could be utilized to develop molecular markers for track and trace of migrations within and between populations. This study illustrates how mitochondrial introns can be used as markers for population genetic analysis. SNP analysis demonstrate the occurrence of mitochondrial recombination in F. asiaticum as was previously found for F. oxysporum and implied for F. graminearum. Furthermore, varying degrees of genetic diversity and recombination showed a high association with different geographic regions as well as with cropping systems. The mitogenome of F. graminearum showed a much higher SNP diversity while the interspecies intron variation showed no evidence of gene flow between the two closely related and sexual compatible species.